How to launch a counter-spy(ware) mission. - Aguilera, Ray (Mac life)
Who needs USB drives with built-in antivirus and data theft protection apps? Anyone with a secret or two. Mac security on a stick--in the form of USB drives preloaded with antivirus and data-theft prevention apps--can guard the info you keep on your computer from all manner of prying eyes and would-be crooks.